2007
DOI: 10.1002/sim.2899
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian modelling of tuberculosis clustering from DNA fingerprint data

Abstract: A combination of continuous and categorical tests, none of which is a gold standard, is often available for classification of subject status in epidemiologic studies. For example, tuberculosis (TB) molecular epidemiology uses select mycobacterial DNA sequences to provide clues about which cases of active TB are likely clustered, implying recent transmission between these cases, versus reactivation of previously acquired infection. The proportion of recently transmitted cases is important to public health, as d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…antenatal antibiotics, uncultivable bacteria as etiological agents, specimen contamination ex-vivo ) increase the odds for EONS misclassification [37]. Our approach of using LCA was aimed to circumvent this obstacle [33], [77]. We established a diagnostic algorithm that adds two CB biochemical markers, (Hp&HpRP switch pattern and IL-6) to the hematological indices used for presumed EONS.…”
Section: Discussionmentioning
confidence: 99%
“…antenatal antibiotics, uncultivable bacteria as etiological agents, specimen contamination ex-vivo ) increase the odds for EONS misclassification [37]. Our approach of using LCA was aimed to circumvent this obstacle [33], [77]. We established a diagnostic algorithm that adds two CB biochemical markers, (Hp&HpRP switch pattern and IL-6) to the hematological indices used for presumed EONS.…”
Section: Discussionmentioning
confidence: 99%
“…8,66 We knew that with respect to funisitis, which is a more precise pathologic entity, our Hp switch-on algorithm had better accuracy (83%) than with the clinical diagnosis of early onset sepsis (73%). Therefore, we used latent class analysis (LCA), 67 a statistical method that has gained increased acceptance for situations when a perfect gold standard diagnostic test does not exist. 68 This analysis assumes that a hidden (latent) variable (which in our case we named: antenatal exposure to intra-amniotic inflammation) is responsible for heterogeneity among observed variables.…”
Section: [A]cord Blood Haptoglobin Switch-on Pattern As Biomarker Of mentioning
confidence: 99%
“…Therefore measures of recent transmission that account for genetic heterogeneity and fingerprint pattern change rate need to be developed to ensure that the sample cluster distribution accurately represents the reality in the population [9]. Scott et al [10] investigated and compared three measures – IS 6110 RFLP, both dichotomous and continuous (nearest genetic distance) and PCR-based. They concluded that the poor sensitivity of the standard IS6110 RFLP test leads to estimates of clustering that are likely too low yet IS6110 typing remains the best method, at least in a low-incidence setting where the population of M. tuberculosis isolates shows a high degree of genetic diversity.…”
Section: Discussionmentioning
confidence: 99%